2012
DOI: 10.1002/jmv.23403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prohibitin as a Chikungunya virus receptor protein

Abstract: Chikungunya virus (CHIKV) has recently re-emerged causing millions of infections in countries around the Indian Ocean. While CHIKV has a broad host cell range and productively infects a number of different cell types, macrophages have been identified as a potential viral reservoir serving to increase the duration of symptoms. To date no CHIKV interacting protein has been characterized and this study sought to identify CHIKV binding proteins expressed on target cell membranes. Two-dimensional virus overlay iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 74 publications
(104 reference statements)
4
147
0
2
Order By: Relevance
“…These later authors also have found evidence that multiple pathways maybe employed by CHIKV to enter into cells, as already proposed with dengue virus (DENV) [67,68]. Another possible explanation could be that there are cell type specific differences implied in the entry mechanism [62].…”
Section: Genomic Organization and Viral Replicationmentioning
confidence: 59%
See 2 more Smart Citations
“…These later authors also have found evidence that multiple pathways maybe employed by CHIKV to enter into cells, as already proposed with dengue virus (DENV) [67,68]. Another possible explanation could be that there are cell type specific differences implied in the entry mechanism [62].…”
Section: Genomic Organization and Viral Replicationmentioning
confidence: 59%
“…The E1 glycoprotein is a class II fusion protein that mediates fusion of the viral and host cell membranes during virus entry, while the E2 glycoprotein is a 50-kDa type I trans-membrane glycoprotein that is responsible for receptor binding to host cells [61,62]. Viral replication is initiated by attachment of viral envelope to host cell receptors [63], followed by low pH-mediated membrane fusion and delivery of the viral nucleocapsid into the cytoplasm (Fig.…”
Section: Genomic Organization and Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIKV replication in these cells induces cytopathic effects which can be used to test its virulence and dissect the detailed steps of virus life cycle. The CHIKV specific entry receptor is yet to be defined, but several putative receptors facilitate virus infection, including Glycosaminoglycans (GAGs), Prohibitin (PHB), Dendritic Cell-Specific Intercellular adhesion molecule (ICAM)-3-Grabbing Non-integrin (DC-SIGN, CD209) and Liver lymph node-specific ICAM-3-grabbing integrin (L-SIGN) (Klimstra et al, 2003;Wintachai et al, 2012;Weber et al, 2017).…”
Section: Cellular Modelsmentioning
confidence: 99%
“…1). 31 Two precursors of non-structural proteins are translated from the viral mRNA,and cleavage of these precursors generates nsP1-nsP4. 32 These proteins assemble to form the viral replication com-plex, which synthesizes a full-length negative-strand RNAintermediate.…”
Section: Virusmentioning
confidence: 99%